Economic integration in North America - an agreement of limited dimensions but unlimited expectations. - GORDON, Michael Wallace (1993)
Notes that while NAFTA appears to be exclusively about trading relationships, it is a document governing relationships. Underlying the text are the relationships of East and West as the relationships within the NAFTA extend outward to Asia. Illegal Mexican immigration, and massive trade deficits, have caused the US to shift its traditional East-West focus to North-South.